Antibacterial Efficacy of Epigallocatechin-3-gallate against Streptococcus mutans: A Systematic Review / Eficacia antibacteriana de la epigalocatequina-3-galato contra el Streptococcus mutans: Revisión Sistemática - Ferreira, Danielly Cunha Araújo (2017)
ABSTRACT. Background: Green tea, obtained from the Camellia sinensis, is one of the most popular drinks worldwide and has recently been in the focus of scientific research due to its beneficial effects on general health. Several studies suggest that, among the polyphenols found on green tea, epigallocatechin-3-gallate (EGCG) is the most bioactive compound and is responsible for its antibacterial activity. Purpose: To conduct a qualitative systematic review of literature evaluating the antibacterial efficacy of EGCG against Streptococcus mutans (S. mutans). Methods: Relevant published studies included in the Pubmed (1966- June 2015), Scopus (1960- June 2015), Web of Science (1900- June 2015), and Google Scholar databases were identified. Publications of in vitro studies, which studied EGCG antibacterial efficacy against S. mutans, were extracted and pooled in a table. The evaluation included inhibition zone measures, reduction of the number of microorganisms, and biofilm formation. Results: Twelve studies were selected to compose this systematic review. Eleven of them showed that EGCG has antibacterial efficacy against S. mutans. Conclusions: In vitro evidence available confirms the antibacterial activity of EGCG against S. mutans.RESUMEN. Antecedentes: El té verde, obtenido de la Camellia sinensis, es una de las bebidas más populares en el mundo y ha estado recientemente en el foco de atención de la investigación científica por sus efectos benéficos en la salud general. Varios estudios sugieren que, entre los polifenoles encontrados en el té verde, la epigalocatequina-3-galato (EGCG) es el compuesto más bioactivo y es el responsable de su actividad antimicrobiana. Objetivo: Realizar una revisión sistemática cualitativa de la literatura donde se evalúe la actividad antibacteriana de la EGCG contra el Streptococcus mutans (S. mutans). Métodos: Se identificaron estudios relevantes incluidos en las bases de datos bibliográficas Pubmed (1966- junio 2015), Scopus (1960- junio 2015), Web of Science (1900- junio 2015) y Google Académico. Los datos de estudios in vitro que investigaron la eficacia antibacterial de la EGCG contra el S. mutans se seleccionaron y organizaron en una tabla. La evaluación de los estudios incluyó los criterios: medidas de las zonas de inhibición, reducción del número de microorganismos y formación de biopelícula. Resultados: Se seleccionaron 12 estudios para la revisión sistemática. Once de ellos comprobaron la eficacia antibacteriana de la EGCG contra el S. mutans. Conclusiones: La evidencia in vitro disponible confirma que la EGCG tiene un efecto antibacteriano contra el S. mutans.